Do you know this syndrome? Leopard syndrome - Flávio Heleno da Silva Queiroz Cançado; Luis Candido Pinto da Silva; Paulo Franco Taitson; Ana Carolina Dias Viana de Andrade; Matheus Melo Pithon; Dauro Douglas Oliveira (Sociedade Brasileira de Dermatologia, 2017)
ABSTRACT Hypertrophic cardiomyopathy is known as Leopard syndrome, which is a mnemonic rule for multiple lentigines (L), electrocardiographic conduction abnormalities (E), ocular hypertelorism (O), pulmonary stenosis (P), abnormalities of genitalia (A), retardation of growth (R), and deafness (D). We report the case of a 12-year-old patient with some of the abovementioned characteristics: hypertelorism, macroglossia, lentigines, hypospadias, cryptorchidism, subaortic stenosis, growth retardation, and hearing impairment. Due to this set of symptoms, we diagnosed Leopard syndrome.